2020
DOI: 10.12973/eu-jer.9.4.1591
|View full text |Cite
|
Sign up to set email alerts
|

Development of E-Learning Oriented Inquiry Learning Based on Character Education in Multimedia Course

Abstract: <p style="text-align: justify;">The study aimed to: 1) determine the e-learning design oriented inquiry learning based on character education in multimedia courses, 2) find out the feasibility of e-learning oriented inquiry learning based on character education in multimedia courses, 3) identify the effectiveness of e-learning oriented inquiry learning based on character education in multimedia courses. This study employed the research and development design. The research and development model used is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 7 publications
0
14
0
2
Order By: Relevance
“…A multicultural-based learning model was developed based on constructivism theory. According to constructivism, knowledge is a human construction (formation) and is not an imitation of reality (Suartama Triwahyuni, Sukardi & Hastuti, 2020). Learning is an active process of learners constructing meaning through the process of assimilating and connecting the experience or learning material with the understanding they already have (Suastika, Mangku, Yuliartini & Wayan Lasmawan, 2020).…”
Section: Syntax Of Multicultural-based Learning Modelmentioning
confidence: 99%
“…A multicultural-based learning model was developed based on constructivism theory. According to constructivism, knowledge is a human construction (formation) and is not an imitation of reality (Suartama Triwahyuni, Sukardi & Hastuti, 2020). Learning is an active process of learners constructing meaning through the process of assimilating and connecting the experience or learning material with the understanding they already have (Suastika, Mangku, Yuliartini & Wayan Lasmawan, 2020).…”
Section: Syntax Of Multicultural-based Learning Modelmentioning
confidence: 99%
“…Where the transition is smooth and successive, traditional face-to-face learning can coexist or is blended with the forms of distance learning. In contrast to the established gradual methods for planning and implementation of courses (Suartama et al, 2020), the transition from face-to-face to online courses observed in the COVID-19 pandemic was driven by an external factor and not by the pedagogical desire to make courses or computer applications (Blumenthal & Blumenthal, 2020) user friendly.…”
Section: Introductionmentioning
confidence: 97%
“…Each value does not stand and develop by itself. They are connected with each other and are developed dynamically to form an individual unity (Suartama, Triwahyuni, Sukardi & Hastuti, 2020).…”
Section: Strengthening Of Character Educationmentioning
confidence: 99%